ITALIAN MUTUAL BANKS: CORPORATE SOCIAL AND FINANCIAL PERFORMANCE - Piatti, Domenico (European Scientific Journal, ESJ, 2014)
The aim of this study is to evaluate the intensity of the relationship between social and financial performance by using a sample of Italian mutual banks. The existence of this potential relation is an issue already investigated in the literature, but with ambiguous results due to the difficulty of defining a univocal social performance measure. This study provides novel evidence on this relationship by employing the canonical correlation method which allows simultaneous account to be taken of several measures for both social and financial performance. Five main dimensions are considered to measure social performance covering the principal stakeholders. The findings suggest that a positive relation exists, but only between some dimensions of both social and financial performance